2019
DOI: 10.4067/s0717-75182019000400400
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre tiempos de alimentación, composición nutricional del desayuno y estado nutricional en estudiantes universitarios de Valparaíso, Chile

Abstract: Se han descrito estilos de vida poco saludables en estudiantes universitarios, como omisión del desayuno, alto consumo de comida rápida y horarios dispersos. El objetivo de este trabajo fue relacionar distintas características de la ingesta alimentaria con el estado nutricional en este grupo. Se realizó un estudio observacional analítico, donde participaron 130 jóvenes sedentarios. Se evaluó el estado nutricional y la ingesta alimentaria. Un 25% de la muestra presentó malnutrición por exceso (IMC), mientras qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 8 publications
0
6
0
17
Order By: Relevance
“…Calories represented 15.4% and 14.2%, respectively, of the total caloric requirement for the subjects, showing values below those recommended for this meal. Concha et al [71] also observed energy intakes below recommendations among university students in Valparaíso, Chile, and showed significant differences according to the body composition of participants. Specifically, participants with low and normal fat percentages, consumed close to 19% of total caloric requirement at breakfast, while participants with excess fat consumed only 8.9% of daily calories at breakfast.…”
Section: Discussionmentioning
confidence: 96%
“…Calories represented 15.4% and 14.2%, respectively, of the total caloric requirement for the subjects, showing values below those recommended for this meal. Concha et al [71] also observed energy intakes below recommendations among university students in Valparaíso, Chile, and showed significant differences according to the body composition of participants. Specifically, participants with low and normal fat percentages, consumed close to 19% of total caloric requirement at breakfast, while participants with excess fat consumed only 8.9% of daily calories at breakfast.…”
Section: Discussionmentioning
confidence: 96%
“…The lived experience of undergraduate student parents: roles compatibility challenge ability to fulfil their maternal/paternal role, in the construction of the previously mentioned selfconcept as a parent, and even influencing the parent-child attachment style; and on the other hand, in their self-perception as a student, which influences their academic performance. (8,20,24) When university policies recognize the unique situation of students being parents and grant them the necessary support to fulfil their dual role, the university environment has the potential to become a setting for enriching experiences that not only promote the integral development of the student, but also positively influence the development of their child and their new family (20) and contribute to a more inclusive university environment. (8,23) Various university institutions have developed specific policies designed to protect and support mothering students, however fewer initiatives exist taking into account that needs of fathering students.…”
Section: Discussionmentioning
confidence: 99%
“…Los universitarios omiten tiempos de comida, siendo el desayuno el que menos se consume y se puede deber a la falta de educación alimentaria, necesidad de adaptarse a un nuevo estilo de vida, horario de clases demandantes, calidad del sueño, sobrecarga de estudios y aspectos socioeconómicos 7,31 . Es de resaltar que cuando un adolescente omite el desayuno, puede sufrir de menor desempeño intelectual e incrementa el riesgo de desarrollar enfermedades en la edad adulta (diabetes mellitus tipo 2, obesidad, enfermedad coronaria, entre otras) 32,33 .…”
Section: Discussionunclassified